Preparation and in-Vitro Evaluation of Cinnarizine Raft Forming Chewable Tablets - Aseel S. Najm; Wedad K. Ali (College of Pharmacy / Mustansiriyah University, 2019)
Cinnarizine is an anti-histaminic drug and is mainly used to treat symptoms accompanying motion sickness like vomiting and dizziness. It has low and variable bioavailability due to its low water solubility. Cinnarizine (weakly basic drug) is formulated as raft forming   chewable Tablets to allow its complete dissolution at the stomach to be absorbed at the upper part of small intestine. Raft forming chewable Tablets are formulated by direct compression method using sodium alginate or pectin as raft forming agents. The prepared Tablets were evaluated for their pre and post- compression parameters and they have shown desirable results regarding evaluation of hardness, thickness, % friability, weight variation, content uniformity, raft strength, weight and volume, in addition to in-vitro drug release. Out of all the prepared formulas F1 selected as the optimum formula with 488.1mg raft strength and 92.34% drug release after 24hrs that is promising for the formulation of the raft system. Cinnarizine is an anti-histaminic drug and is mainly used to treat symptoms accompanying motion sickness like vomiting and dizziness. It has low and variable bioavailability due to its low water solubility. Cinnarizine (weakly basic drug) is formulated as raft forming   chewable Tablets to allow its complete dissolution at the stomach to be absorbed at the upper part of small intestine. Raft forming chewable Tablets are formulated by direct compression method using sodium alginate or pectin as raft forming agents. The prepared Tablets were evaluated for their pre and post- compression parameters and they have shown desirable results regarding evaluation of hardness, thickness, % friability, weight variation, content uniformity, raft strength, weight and volume, in addition to in-vitro drug release. Out of all the prepared formulas F1 selected as the optimum formula with 488.1mg raft strength and 92.34% drug release after 24hrs that is promising for the formulation of the raft system.